Analisis Dampak Perubahan Dasar Pungutan Pajak Terhadap Perekonomian Indonesia - Johanes Wahyu Galandjindjinay; I Dewa Gde Dana Sugama (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
This paper aims to evaluate the impact of changes in the tax base on Indonesia's economy. It begins by providing an overview of Indonesia's taxation system and recent changes in tax policy. The paper then discusses the effects of tax base changes on economic variables such as investment, government revenue, and economic growth. Using empirical data and economic models, this study assesses the short-term and long-term impacts of tax changes on key economic indicators. The findings indicate that while tax reforms can stimulate economic activity in the short term, their long-term effects depend on various factors such as tax structure, administrative efficiency, and economic conditions. The paper concludes with policy implications and recommendations for policymakers in Indonesia.